Optimisasi Budidaya Rumput Laut sebagai Benteng Alami untuk Mengurangi Asidifikasi Laut - Moch Altof Maulana; Firra Rosariawari (Yayasan Literasi Sains Indonesia, 2024)
Anthropogenic carbon dioxide emissions are propelling a concerning rise in ocean acidity, posing severe threats to marine ecosystems, especially calcifying organisms like corals and mollusks. In response to this global challenge, seaweed farming has emerged as a promising remedy. Leveraging their remarkable growth rates and carbon sequestration abilities, seaweeds offer a viable solution to counteract the acidifying effects of elevated carbon dioxide levels in the oceans. Through photosynthesis, seaweeds actively absorb carbon dioxide from seawater, thereby mitigating acidity and fostering improved water quality. The potential of seaweed farms extends beyond mere carbon sequestration. These farms play a pivotal role in habitat creation, absorb nitrogen and phosphorus nutrients, and contribute to enhanced biodiversity. The cultivation of seaweed not only addresses the immediate concern of ocean acidification but also provides a holistic ecological approach with far-reaching benefits. As a sustainable and scalable strategy, seaweed farming exemplifies an innovative and multifaceted solution to the complex challenges posed by anthropogenic impacts on the oceans, underlining the importance of nature-based interventions in preserving the health and balance of marine ecosystems.